2019
DOI: 10.18632/aging.102080
|View full text |Cite
|
Sign up to set email alerts
|

CCAT1 promotes triple-negative breast cancer progression by suppressing miR-218/ZFX signaling

Abstract: Long non-coding RNAs (lncRNAs) regulate cancer development and progression. Here, we investigated the role of the lncRNA CCAT1 in triple-negative breast cancer (TNBC). CCAT1 expression was higher in TNBC cells than normal breast epithelial cells. Additionally, CCAT1 expression was higher in TNBC patient tumor tissue than adjacent normal breast tissue. Silencing CCAT1 inhibited TNBC cell proliferation, migration, and invasion in vitro , and tumor growth and progression in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…It is now well established that lncRNAs are important regulators of human diseases. Previous studies have shown that lncRNA CCAT1 is upregulated in a series of cancers, including colorectal cancer (Nissan et al, 2012), non-small cell lung cancer (Luo et al, 2014), breast cancer (Han et al, 2019), hepatocellular carcinoma (Guo et al, 2019), gastric cancer (Li Y. et al, 2019), gallbladder cancer (Ma et al, 2015), acute myeloid leukemia (Chen et al, 2016), endometrial carcinoma (Yu et al, 2019), nasopharyngeal carcinoma (Dong et al, 2018), and cervical cancer (Shen et al, 2019). In this study, we found that the expression of CCAT1 was significantly increased in LAD tissues than that of adjacent non-tumor tissues.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It is now well established that lncRNAs are important regulators of human diseases. Previous studies have shown that lncRNA CCAT1 is upregulated in a series of cancers, including colorectal cancer (Nissan et al, 2012), non-small cell lung cancer (Luo et al, 2014), breast cancer (Han et al, 2019), hepatocellular carcinoma (Guo et al, 2019), gastric cancer (Li Y. et al, 2019), gallbladder cancer (Ma et al, 2015), acute myeloid leukemia (Chen et al, 2016), endometrial carcinoma (Yu et al, 2019), nasopharyngeal carcinoma (Dong et al, 2018), and cervical cancer (Shen et al, 2019). In this study, we found that the expression of CCAT1 was significantly increased in LAD tissues than that of adjacent non-tumor tissues.…”
Section: Discussionsupporting
confidence: 52%
“…LncRNA colon cancer-associated transcript-1(CCAT1) was significantly upregulated in colon cancer tissue and cells (Nissan et al, 2012). Recently, CCAT1 has been studied in various cancers (Guo and Hua, 2017;Shi et al, 2017;Han et al, 2019;Hu et al, 2019;. CCAT1 plays a role in promoting the proliferation and invasion of cervical cancer by regulating the miR-181a-5p/MMP14 axis (Shen et al, 2019) and promotes endometrial carcinoma progression by miR-181a-5p (Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Colon cancer-associated transcript-1 (CCAT1) was first studied in colon cancer and subsequently in other cancers, including breast cancer [75,101]. In spheroid culture, breast cancer cells had a higher expression of CCAT1 [74].…”
Section: Ccat1mentioning
confidence: 99%
“…The ceRNA pattern was widely observed in TNBC progression. Silenced CCAT1 inhibited TNBC cell proliferation, migration, and invasion through endogenously sponging miR-218 to elevate ZFX expression 2 . LINC01133 promotes phenotypic and growth characteristics of cancer stem cell-like cells via mediating the miR-199a/FOXP2 axis in TNBC cells 3 .…”
Section: Introductionmentioning
confidence: 99%